2019
DOI: 10.1177/1060028019852601
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Capsaicin for the Treatment of Cannabinoid Hyperemesis Syndrome: A Systematic Review

Abstract: Objective: Cannabinoid hyperemesis syndrome (CHS) is characterized by cyclic vomiting, abdominal pain, and alleviation of symptoms via hot showers in chronic cannabinoid users. Capsaicin is recommended as a reasonable first-line treatment approach for CHS despite limited clinical evidence regarding its use. The objective of this study is to systematically review the efficacy data for capsaicin in CHS. Data Sources: A literature search using keywords related to cannabinoids, emesis, and capsaicin was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 66 publications
0
17
1
4
Order By: Relevance
“…There is apparent enthusiasm for capsaicin in managing CHS in the emergency medicine community based on multiple case reports and retrospective studies. [11][12][13][14][15]21 While our results did not demonstrate rapid resolution of nausea as predicted, we suggest Peptic ulcer disease 1 (5. that capsaicin may have a physiological effect on nausea and should spur further research in this area. Due to the widespread availability and low cost of capsaicin, it remains an intriguing therapeutic option for managing nausea and vomiting associated with CHS.…”
Section: Discussioncontrasting
confidence: 61%
“…There is apparent enthusiasm for capsaicin in managing CHS in the emergency medicine community based on multiple case reports and retrospective studies. [11][12][13][14][15]21 While our results did not demonstrate rapid resolution of nausea as predicted, we suggest Peptic ulcer disease 1 (5. that capsaicin may have a physiological effect on nausea and should spur further research in this area. Due to the widespread availability and low cost of capsaicin, it remains an intriguing therapeutic option for managing nausea and vomiting associated with CHS.…”
Section: Discussioncontrasting
confidence: 61%
“…A 2019 systematic review by McConchaie et al [34] that included 95 adult and pediatric patients found that capsaicin cream was beneficial in the treatment of CHS in all patients for whom it had been administered, but found no significant benefit for capsaicin cream on primary outcomes, including length of ED stay [34]. Two of the patients included in this systematic review were also included in the present review.…”
Section: Discussionmentioning
confidence: 90%
“…Capsaicin cream and haloperidol are two emerging therapeutic options for the active treatment of abdominal pain that were described to be effective in a few studies. In two case reports by McConachie et al [34] and Graham et al [31], capsaicin cream was found to be an effective second-line treatment for two patients who had received .025% capsaicin cream applied to the abdomen. One patient received ondansetron in conjunction with the capsaicin cream and achieved symptom resolution after 30 minutes, whereas the positive outcomes of the other patient were attributed to only the capsaicin cream, which was applied independently following the failure of 4 mg of ondansetron administered sublingually and 5 mg of oral oxycodone to improve nausea and pain, respectively.…”
Section: Treatmentmentioning
confidence: 97%
“…While compulsive hot water bathing is a way to relieve symptoms through peripheral vasodilation, by diverting splanchnic circulation, several trials have proposed the use of topical capsaicin 0.075% concentration applied to abdomen or back of arms as an adjunct to treat CHS. This occurs through activation of TRPV1 receptors, neurohumoral regulation, and modulation of specific neurotransmitters such as histamine, acetylcholine, and serotonin 67,73,74 . It is important to be cautious when applying this treatment since it can produce significant skin irritation or chemical burns.…”
Section: Proposed Managementmentioning
confidence: 99%